2006
DOI: 10.1097/01.jcp.0000195113.61291.48
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate Treatment for Women With Borderline Personality Disorder

Abstract: Borderline personality disorder is a common and severe psychiatric illness. The goal of this study was to determine whether topiramate can influence patients' borderline psychopathology, health-related quality of life, and interpersonal problems. Women meeting the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition Structured Clinical Interview II criteria for borderline personality disorder were randomly assigned in a 1:1 ratio to topiramate titrated from 25 to 200 mg/d (n = 28) or placebo (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(39 citation statements)
references
References 34 publications
0
36
0
3
Order By: Relevance
“…Sin embargo, el estudio tuvo una corta duración, excluyéndose los casos con tendencias suicidas. En otros dos estudios se estableció que el topiramato se asociaba a disminución de irritabilidad, rabia, hostilidad, sensibilidad interpersonal, ansiedad fóbica y severidad global de la enfermedad 59,60 .…”
Section: Topiramatounclassified
“…Sin embargo, el estudio tuvo una corta duración, excluyéndose los casos con tendencias suicidas. En otros dos estudios se estableció que el topiramato se asociaba a disminución de irritabilidad, rabia, hostilidad, sensibilidad interpersonal, ansiedad fóbica y severidad global de la enfermedad 59,60 .…”
Section: Topiramatounclassified
“…Topiramate and lamotrigine have both been shown in small RCTs to be effective in the treatment of symptoms of aggression in BPD [Nickel et al , 2004Tritt et al 2005]. In addition, there is evidence from one placebo-controlled trial of a broader effect of topiramate in treating other symptoms of BPD, including interpersonal problems and anxiety [Loew et al 2006]. Two small RCTs have demonstrated efficacy for divalproex sodium in the treatment of BPD [Hollander et al 2001], or BPD with comorbid bipolar II disorder [Frankenberg and Zanarini, 2002].…”
Section: Antidepressantsmentioning
confidence: 99%
“…A third 10-week RCT on topiramate (25-200 mg/day) conducted by Loew et al [48] in 56 females with BPD and concurrent mood disorders reported a significant reduction in somatization symptoms, interpersonal sensitivity, and hostility. Furthermore, an improvement of global functioning emerged from this set of data.…”
Section: ) Mood Stabilizersmentioning
confidence: 99%